Task-based language teaching to develop productive skills in EFL - Amaya Noguera, Cecia Judith (2021)
The present research work is focused on the implementation of Task-Based Language Teaching approach to develop productive skills at rural school. The importance of communication in English has increased in different spheres of our society. In our educational system, English has been taught for many years, but the productive skills are not well developed in the students especially at rural schools. Taking into account that speaking and writing are difficult skills to be developed in language acquisition, this research work is designed to develop self-confidence, motivation and creativity according to learners’ needs, age, context, and preferences. Proper planning, implementation and monitoring can give learners the opportunity to achieve language proficiency in productive skills. This research work shows the different task-based learning principles and tasks to be used with the purpose of developing and verifying the effectiveness of the strategies and activities of this approach to promote the development of speaking and writing allowing the learners to be the protagonists and creators of their own language learning process.